2018
DOI: 10.4066/biomedicalresearch.29-17-426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retention of dental students' trauma knowledge following a reminder lecture

Abstract: Aim: The aim of this study was to assess senior dental students' acquisition of knowledge after 3 months following a reminder lecture. Materials and methods: A 1 h lecture including a slide presentation was prepared according to the Guidelines of International Association of Dental Traumatology (IADT). The participants were asked to fill-out a questionnaire of 31 questions before (T0), after (T1) and 3 months (T2) after the lecture and were given 15 min for the completion of each questionnaire. Statistical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The opportunity for dentistry students to encounter a traumatic injury during undergraduate education depends on a variety of factors, whereas incidents are managed by specialists or post-graduate students, leaving the dentistry students with very little opportunity to be directly involved in the treatment process, and to acquire sufficient clinical competency prior to graduation [22]. The step-by-step concept used in the mobile application in this research helped students to improve their understanding on management of injuries of both deciduous and permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity for dentistry students to encounter a traumatic injury during undergraduate education depends on a variety of factors, whereas incidents are managed by specialists or post-graduate students, leaving the dentistry students with very little opportunity to be directly involved in the treatment process, and to acquire sufficient clinical competency prior to graduation [22]. The step-by-step concept used in the mobile application in this research helped students to improve their understanding on management of injuries of both deciduous and permanent teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated lectures were found to be effective at improving the knowledge and retention of knowledge. The retention of knowledge concerning dental trauma was higher after reminder lectures than before the lecture in undergraduate students [ 22 , 23 ]. AlZoubi et al suggested that dental trauma education should be held as a mandatory course for the dental practitioner to take annually or biannually [ 23 ].…”
Section: Discussionmentioning
confidence: 99%